Basic competencies of the graduates of BRAC non-formal primary schools declining - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
Based on the Declaration of the World Conference on Education for All held in Jomtien in 1990, BRAC designed an instrument to measure the level of basic education of Bangladeshi children. The Research and Evaluation Division of BRAC regularly monitors the performance of the graduates of BRAC's non-formal primary schools through this instrument. The instrument has four sections - reading, writing, numeracy and life skills knowledge. A respondent satisfying the set criteria in all the four areas was considered as having basic education. This report presents the basic educational status of the graduates of four cohorts of 1995, 1997, 1999 and 2001. Four independent samples were drawn from these four cohorts and the graduates were tested after nine/ten months of their graduation. Besides, re-test of the previously assessed graduates were done during the following surveys. Sampling design was similar in each survey. Children from three types of BRAC schools were assessed, these are Non Formal Primary Education (NFPE) and Basic Education for Older Children (BEOC) directly run by BRAC Education Programme, and NFPE under the Education Support Programme (ESP) operated by other NGOs with support from BRAC. The sample size for the four independent surveys was about 1,260 each. Not all former graduates were found in the re-surveys, for instance only a third of the graduates of 1995 were common in all the four surveys.